Perceptions of Teachers Toward Deep Learning as an Outcome of the Meaningful and Joyful Learning Training Program - Fatah, Amir; Tafakur, Tafakur; Sutiman, Sutiman; Sriyanto, Joko; Mauzino, Albino; Fatin, Nabila Naila (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
The implementation of deep learning in Indonesian junior high schools remains challenging due to teachers’ limited understanding and practical readiness. This community service program aimed to enhance teachers’ knowledge of deep learning principles within the Merdeka Curriculum and to support them in developing deep learning-based teaching materials. The program involved training and mentoring 46 teachers from two public junior high schools in Yogyakarta using workshops, guided practice, and follow-up support. Data were collected through a knowledge quiz, a participant satisfaction questionnaire, and document analysis of the developed learning modules. The results show that teachers achieved a good level of understanding of deep learning concepts (mean score = 8.1), expressed high satisfaction with the program, and successfully produced learning modules that reflected key characteristics of deep learning and were ready for classroom use. These findings indicate that structured professional development can effectively support teachers in implementing deep learning within the Merdeka Curriculum and may serve as a practical model for similar school-based training programs.